Molecular evidence confirms the relationship of Petrocelis in the western Atlantic to Mastocarpus stellatus (Rhodophyta, Petrocelidaceae) - Bird, C. J.; Sosa, P. A.; MacKay, R. M. (Phycologia, 1994)
137 134 SCIE